Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph192113757
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Fasting and Non-Fasting Participants: The UAE Healthy Future Study

Abstract: Introduction: Metabolic syndrome (MetS) is a multiplex of risk factors that predispose people to the development of diabetes and cardiovascular disease (CVD), two of the major non-communicable diseases that contribute to mortality in the United Arab Emirates (UAE). MetS guidelines require the testing of fasting samples, but there are evidence-based suggestions that non-fasting samples are also reliable for CVD-related screening measures. In this study, we aimed to estimate MetS and its components in a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Hypertension is also one of the major NCDs and a public health challenge that increases the risk of developing CVD [20]. The Gulf region has become one of the most affected regions by hypertension, and the prevalence ranges from 26.1% in Saudi Arabia to 37% in Kuwait [20]. Among the UAE population, a cross-sectional study found that 22.4% were hypertensive, and men had higher blood pressure than women [20].…”
Section: Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypertension is also one of the major NCDs and a public health challenge that increases the risk of developing CVD [20]. The Gulf region has become one of the most affected regions by hypertension, and the prevalence ranges from 26.1% in Saudi Arabia to 37% in Kuwait [20]. Among the UAE population, a cross-sectional study found that 22.4% were hypertensive, and men had higher blood pressure than women [20].…”
Section: Hypertensionmentioning
confidence: 99%
“…The Gulf region has become one of the most affected regions by hypertension, and the prevalence ranges from 26.1% in Saudi Arabia to 37% in Kuwait [20]. Among the UAE population, a cross-sectional study found that 22.4% were hypertensive, and men had higher blood pressure than women [20]. The Weqaya Program in Abu Dhabi showed an overall prevalence of hypertension of 23.1% [14].…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the 2020 report by the World Health Organization, around 19.1 million people, which accounts for 32% of global deaths, passed away due to cardiovascular comorbidities [1]. Indeed, the increased prevalence of overweight, obesity, and obesity-related cardiometabolic risk factors such as hypertension, glucose, and lipid metabolism dysregulation are associated with a 2-fold increase in CVD events (coronary heart disease, stroke, heart failure) risk and a 1.5-fold mortality increase [2]. Unhealthy lifestyles such as tobacco use, alcohol consumption, physical inactivity, and consuming ultra-processed foods have caused obesity rates to triple over the last 30 years [1].…”
Section: Introductionmentioning
confidence: 99%